Analisis Skrining Kesehatan Calon Pendonor untuk Meningkatkan Minat Donor Darah Masyarakat Patangpuluhan - Suhada, Reza Iqbal; Mumpuni, Nurpuji; Asgiani , Piping (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: Blood donation activities can be carried out by all people aged 17 to 60 years old with a healthy body condition. Before donating blood, a health screening examination is carried out. Most of society has not know what health screening examinations are carried out before donating blood. The purpose of this research is to find out the results health screening examination at Patangpuluhan Community, Wirobrajan, Kota Yogyakarta before donating blood. Method: The sample in this research used total sampling. This research is a descriptive analytical research. Data analysis using the SPSS application with descriptive analytical tests. Result: The results of data analysis show that the characteristics of donors are mostly aged 20-29 years, 8 donors (32%), male gender, 15 donors (60%), private sector employees, 15 donors (32%). Blood type O 12 (48%), weight 61-70 9 (36%), normal blood pressure 22 (88%), normal hemoglobin level 22 (88%). Conclusion: 20 donors were interested in donating blood (80%).